2023
DOI: 10.1111/1749-4877.12750
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive ecology of the black rat (Rattus rattus) in Madagascar: the influence of density‐dependent and ‐independent effects

Abstract: The black rat (Rattus rattus) poses a severe threat to food security and public health in Madagascar, where it is a major cause of pre‐ and post‐harvest crop losses and an important reservoir for many zoonotic diseases, including plague. Elsewhere, ecologically based rodent management (EBRM) strategies have been developed using ecological information to inform decisions on where and when to target control. EBRM could deliver improved health and well‐being outcomes in Madagascar if adapted to the local ecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Based on the results, it was concluded that high rainfall during the early stages of crop production provide ideal conditions for rodents in the rainy season (Scobie et al, 2023). The spatio-temporal patterns in R. rattus breeding activity also established a decline in breeding rates with an increase in population density in crop fields (Scobie et al, 2024).…”
Section: Reproductive Ecology Of Rodentsmentioning
confidence: 93%
“…Based on the results, it was concluded that high rainfall during the early stages of crop production provide ideal conditions for rodents in the rainy season (Scobie et al, 2023). The spatio-temporal patterns in R. rattus breeding activity also established a decline in breeding rates with an increase in population density in crop fields (Scobie et al, 2024).…”
Section: Reproductive Ecology Of Rodentsmentioning
confidence: 93%
“…Related to this case study, research on the breeding dynamics of R. rattus in agricultural systems in the Central Highlands of Madagascar demonstrated the importance of detailed knowledge of the biology and ecology of your pest rodent species in various habitats (from fields to households) and during different seasons before applying management (Scobie et al. 2023). Such an understanding provides insights into the best times to apply EBRM and avoids unintended consequences that may arise if there are density‐dependent and density‐independent responses in population dynamics.…”
Section: Rodent Zoonoses—a One‐health Approachmentioning
confidence: 98%